THE ROLE OF GUIDANCE AND COUNSELLING IN STRENGTHENING STUDENT DISCIPLINE IN SENIOR HIGH SCHOOLS IN SENE EAST DISTRICT OF GHANA - Gabriel Amponsah Adu; Srivastava, Sujata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The study explores the role of guidance and counselling in bolstering student discipline across the two public senior high schools in Sene East District, Ghana. A total of 2,897 participants, including headmasters, school counsellors, teachers, and students, formed the study population. A sample size of 310 was used, comprising randomly selected students, teachers, headmasters, and school counsellors. This sample size constitutes 10% of the total population. The study employed a questionnaire which experts at the University of Education in Winneba validated. The data were analysed through descriptive statistics. The findings indicated that there is a dynamic teacher-student interaction in schools. However, it highlighted inadequate computer facilities within the guidance and counselling setup. Despite improvements in discipline and academic performance attributed to guidance and counselling, challenges such as a lack of legal framework, shortage of trained teacher counsellors, and excessive workload were evident. The study highlights the importance of fostering dialogue and nurturing strong relationships among students, counsellors, teachers, and administrators to promote effective conflict resolution and enhance overall discipline.